Susceptibility of asthmatic children to respiratory infection Susceptibilidade de crianças asmáticas a infecções respiratórias - Júlio C. R. Pereira; Maria Mercedes L. Escuder (Universidade de São Paulo, 1997)
OBJECTIVE: A case-control study of patients with pneumonia was conducted to investigate whether wheezing diseases could be a risk factor. METHODS: A random sample was taken from a general university hospital in S. Paulo City between March and August 1994 comprising 51 cases of pneumonia paired by age and sex to 51 non-respiratory controls and 51 healthy controls. Data collection was carried out by two senior paediatricians. Diagnoses of pneumonia and presence of wheezing disease were independently established by each paediatrician for both cases and controls. Pneumonia was radiologically confirmed and repeatability of information on wheezing diseases was measured. Logistic regression analysis was used to identify risk factors. RESULTS: Wheezing diseases, interpreted as proxies of asthma, were found to be an important risk factor for pneumonia with an odds ratio of 7.07 (95%CI= 2.34-21.36), when the effects of bedroom crowding (odds ratio = 1.49 per person, 95%CI= 0.95-2.32) and of low family income (odds ratio = 5.59 against high family income, 95%CI= 1.38-22.63) were controlled. The risk of pneumonia attributable to wheezing diseases is tentatively calculated at 51.42%. CONCLUSION: It is concluded that at practice level asthmatics should deserve proper surveillance for infection and that at public health level pneumonia incidence could be reduced if current World Health Organisation's guidelines were reviewed as to include comprehensive care for this illness. OBJETIVO: Investigar, através de um estudo caso-controle de pacientes com pneumonia, se as doenças chiadoras poderiam constituir-se em fator de risco. MÉTODOS: De um hospital universitário, na cidade de São Paulo, Brasil, entre março e agosto de 1994, foi tomada uma amostra de 51 casos de pneumonia pareados por sexo e idade a 51 controles sadios e 51 controles não respiratórios. O diagnóstico de pneumonia e a presença de doença chiadora foram investigados de forma independente por cada pediatra tanto para casos quanto para controles. Foi confirmada pneumonia radiologicamente e a repetibilidade da informação sobre doença chiadora foi medida. Foi utilizada regressão logística para identifição de riscos. RESULTADOS: As doenças chiadoras, entendidas como representantes de asma, mostraram ser importante fator de risco para pneumonia, com um odds ratio de 7,07 (IC95%= 2,34-21,36), controlados os efeitos de aglomeração no quarto de dormir (odds ratio de 1,49 por pessoa a mais no quarto, IC95%= 0,95-2,32) e a baixa renda familiar (odds ratio de 5,59 contra alta renda familiar, IC95%= 1,38-22,63). O risco atribuível às doenças chiadoras foi calculado de forma exploratória em 51,42%. CONCLUSÃO: Conclui-se que os clínicos devem ter atenção sobre asmáticos para o risco de infecção e que ao nível da saúde pública a incidência de pneumonia poderia ser reduzida se as orientações atuais da Organização Mundial da Saúde pudessem ser revistas para oferecer atenção integral para os doentes.